The Virtual Touch Toolkit: An Interactive Media Mobile Application for Promoting Well-Being through Affective and Social Touch - Najm, Ali; Hadjipanayi, Christos; Michael-Grigoriou, Despina; Banakou, Domna; McGlone, Francis; Fairhurst, Merle (My University, 2022)
The 'Virtual Touch Toolkit' is the exergame bundle of a newly developed smartphone application for mental health. The primary aim of the exercises is to promote self-discovery by focusing on social, affective touch. The necessity of acknowledging the undervalued properties of affective touch in this day and age is more important than ever as a global pandemic is provoking societal changes that are predicted to be detrimental to our mutual need for affective touch. The toolkit comprises multiple features and sets of exercises, which are designed to stimulate the user's oxytocinergic and reward systems while offering educational insights on affective touch.
Keywords: computer games; diseases; educational aids; mobile computing; smart phones; User interfaces; virtual reality